2012
DOI: 10.1007/s12346-012-0069-x
|View full text |Cite
|
Sign up to set email alerts
|

Geometry of Weak Stability Boundaries

Abstract: The notion of a weak stability boundary has been successfully used to design low energy trajectories from the Earth to the Moon. The structure of this boundary has been investigated in a number of studies, where partial results have been obtained. We propose a generalization of the weak stability boundary. We prove analytically that, in the context of the planar circular restricted three-body problem, under certain conditions on the mass ratio of the primaries and on the energy, the weak stability boundary abo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…When Î P S R 0 2 for = t t 1 , this implies it lies in the three-dimensional region bounded by M u 1 . Moreover, for > t t 1 , due to the separatrix property, P 0 stays within this region inside M u 1 for all time moving forward [21]. This manifold stays within a bounded region, 1 M , bounded by the following: S R 2 , the boundary of H 1 (a zero velocity curve), and a two-dimensional McGehee torus, T M , about P 1 [18,21] 6 .…”
Section: Whenmentioning
confidence: 94%
See 1 more Smart Citation
“…When Î P S R 0 2 for = t t 1 , this implies it lies in the three-dimensional region bounded by M u 1 . Moreover, for > t t 1 , due to the separatrix property, P 0 stays within this region inside M u 1 for all time moving forward [21]. This manifold stays within a bounded region, 1 M , bounded by the following: S R 2 , the boundary of H 1 (a zero velocity curve), and a two-dimensional McGehee torus, T M , about P 1 [18,21] 6 .…”
Section: Whenmentioning
confidence: 94%
“…A purely analytic proof for the global manifold stricture about P 2 and  k is not available at this time. However, in the case of motion about P 1 , the analogous structure of  k is analytically proven [21].…”
mentioning
confidence: 99%
“…Much work on studying transfer dynamics in celestial mechanics exploits these tools. See for example [2,3,4,8,9,10,11,12,33,40,41]. The study of invariant manifolds for periodic orbits also plays a role in the study of biological and chemical oscillations, and we refer for example to the work of [15,13,17,16,72].…”
Section: Related Workmentioning
confidence: 99%
“…Such symbolic dynamics has been proved using rigorous computer assisted computations by Wilczak and Zgliczyński [23,24]. In recent papers of Belbruno, Gidea, and Topputo [4,5] it is shown that the weak stability boundary method and the invariant manifold method coincide.…”
Section: Introductionmentioning
confidence: 97%